Effect of water content on thermal behavior of freeze-dried soy whey and their isolated proteins - Sobral, Pablo Antonio (2011)
Thermal behavior of lyophilized soy whey (LSW) and whey soy proteins (WSP) at different water contents (WC) was studied by DSC. In anhydrous condition, Kunitz trypsin inhibitor (KTI) and lectin (L) were more heat stable for WSP with respect to LSW sample. The increase of WC destabilized both proteins but differently depending on the sample analyzed. Thermal stability inversion of KTI and L was observed for WSP and LSW at 50.0% and 17.0% WC, respectively, which correspond to the same water-protein content mass ratio (W/P ≈ 1.9). At W/P < 1.9, KTI was more heat stable than L. Before the inversion point, WC strongly modified the peak temperatures (Tp) of KTI and L for WSP, whereas this behavior was not observed for LSW. The high sugar content was responsible for the thermal behavior of KTI and L in LSW under anhydrous condition and low WC. These results have important implications for the soy whey processing and inactivation of antinutritional factors.